Hydrogen bonding interaction between active methylene hydrogen atoms and an anion as a binding motif for anion recognition: experimental studies and theoretical rationalization - Agarwalla, Hridesh; Jana, Kalyanashis; Maity, Arunava; Kesharwani, Manoj K.; Ganguly, Bishwajit; Das, Amitava (Journal of Physical Chemistry A, 2014)
Two new reagents, having similar spatial arrangements for hydrogen atoms of the active methylene functionalities, were synthesized and interactions of such reagents with different anionic analytes were studied using electronic spectroscopy as well as by using 1H and 31P NMR spectroscopic methods. Experimental studies revealed that these two reagents showed preference for binding to F– and OAc–. Detailed theoretical studies along with the above-mentioned spectroscopic studies were carried out to understand the contribution of the positively charged phosphonium ion, along with methylene functionality, in achieving the observed preference of these two receptors for binding to F– and OAc–. Observed differences in the binding affinities of these two reagents toward fluoride and acetate ions also reflected the role of acidity of such methylene hydrogen atoms in controlling the efficiencies of the hydrogen bonding in anion–Hmethylene interactions. Hydrogen bonding interactions at lower concentrations of these two anionic analytes and deprotonation equilibrium at higher concentration were observed with associated electronic spectral changes as well as visually detectable change in solution color, an observation that is generally common for other strong hydrogen bond donor functionalities like urea and thiourea. DFT calculations performed with the M06/6-31+G**//M05-2X/6-31G* level of theory showed that F– binds more strongly than OAc– with the reagent molecules. The deprotonation of methylene hydrogen atom of receptors with F– ion was observed computationally. The metal complex as reagent showed even stronger binding energies with these analytes, which corroborated the experimental results.

Highly emissive organic solids with remarkably broad color tunability based on N,C-chelate, four-coordinate organoborons - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Thorat, Shridhar; Maity, Arunava; Kulkarni, Prasad P.; Gonnade, Rajesh G.; Munshi, Parthapratim; Patil, Nitin T. (Chemical Communications, 2015)
Molecular fluorophores based on N,C-chelate, four-coordinate organo-borons exhibit tunable solid-state emission colors that cover the whole visible region from blue to red. The emission color can be tuned through the substituents on either quinolines or the boron center.

Specific reagent for Cr(III): imaging cellular uptake of Cr(III) in Hct116 cells and theoretical rationalization - Ali, Firoj; Saha, Sukdeb; Maity, Arunava; Taye, Nandaraj; Si, Mrinal Kanti; Suresh, E.; Ganguly, Bishwajit; Chattopadhyay, Samit; Das, Amitava (Journal of Physical Chemistry B, 2015)
A new rhodamine-based reagent (L-1), trapped inside the micellar structure of biologically benign Triton-X 100, could be used for specific recognition of Cr(III) in aqueous buffer medium having physiological pH. This visible light excitable reagent on selective binding to Cr(III) resulted in a strong fluorescence turn-on response with a maximum at similar to 583 nm and tail of that luminescence band extended until 650 nm, an optical response that is desired for avoiding the cellular autofluorescence. Interference studies confirm that other metal ions do not interfere with the detection process of Cr(III) in aqueous buffer medium having pH 7.2. To examine the nature of binding of Cr(III) to L-1, various spectroscopic studies are performed with the model reagent L-1 which tend to support Cr(III)-eta(2)-olefin pi-interactions involving two olefin bonds in molecular probe L-1. Computational studies are also performed with another model reagent L-M to examine the possibility of such Cr(III)-eta(2)-olefin pi-interactions. Presumably, polar functional groups of the model reagent L-M upon coordination to the Cr(III) center effectively reduce the formal charge on the metal ion and this is further substantiated by results of the theoretical studies. This assembly is found to be cell membrane permeable and shows insignificant toxicity toward live colon cancer cells (Hct116). Confocal laser scanning microscopic studies further revealed that the reagent L-1 could be used as an imaging reagent for detection of cellular uptake of Cr(III) in pure aqueous buffer medium by Hct116 cells. Examples of a specific reagent for paramagnetic Cr(III) with luminescence ON response are scanty in the contemporary literature. This ligand design helped us in achieving the turn on response by utilizing the conversion from spirolactam to an acyclic xanthene form on coordination to Cr(III).

Tuning of multiple luminescence outputs and white-light emission from a single gelator molecule through an ESIPT coupled AIEE process - Maity, Arunava; Ali, Firoj; Agarwalla, Hridesh; Anothumakkool, Bihag; Das, Amitava (Chemical Communications, 2015)
A unique example of an ESIPT coupled AIEE process, associated with a single molecule (1), is utilized for generating multiple luminescent colors (blue-green-white-yellow). The J-aggregated state of 1 forms a luminescent gel in THF and this luminescent property is retained even in the solid state.

[2]Pseudorotaxane formation with fret based luminescence response: demonstration ofboolean operations through self sorting on solid surface - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Das, Amitava (Journal of Organic Chemistry, 2016)
Binary pseudorotaxane formation between an aza crown derivative as host (H) and two different imidazolium derivatives as guests (G(1) and G(2)) have been studied in detail by NMR (H-1 NMR, 2D NOESY), optical (steady state electronic and emission spectroscopy), and mass spectroscopy. Binding stoichiometry (1:1), association constant for the respective [2]pseudorotaxane formation (K-a(H center dot G1) = (2.61 +/- 0.015) X 10(3) M-1 and K-a(H center dot G2) = (1.27 +/- 0.16) X 10(3) M-1), and associated thermodynamic parameters are also evaluated based on isothermal titration calorimetric (ITC) studies. FRET based luminescence ON responses are observed on formation of the binary pseudorotaxane (H center dot G(1) and H center dot G(2)) in a nonpolar medium like dichlororriethane. The thermodynamic feasibility of such an energy transfer process is also examined. The higher affinity of H and 18-crown-6 toward K+, as compared to those toward G(1) or G(2), and the reversibility in the host- guest binding process are utilized in demonstrating the self-sorting phenomena with associated changes in luminescence responses that could be correlated for Boolean operators like YES, INHIBIT, OR, and AND gates.

Counteranion driven homochiral assembly of a cationic C-3-symmetric gelator through ion-pair assisted hydrogen bond - Maity, Arunava; Gangopadhyay, Monalisa; Basu, Arghya; Aute, Sunil; Babu, Sukumaran Santhosh; Das, Amitava (Journal of the American Chemical Society, 2016)
The helical handedness in achiral self-assemblies is mostly complex due to spontaneous symmetry breaking or kinetically controlled random assembly formation. Here an attempt has been made to address this issue through chiral anion exchange. A new class of cationic achiral C-3-symmetric gelator devoid of any conventional gelation assisting functional units is found to form both right-and left-handed helical structures. A chiral counteranion exchange-assisted approach is successfully introduced to control the chirality sign and thereby to obtain preferred homochiral assemblies. Formation of anion-assisted chiral assembly was confirmed by circular dichroism (CD) spectroscopy, microscopic images, and crystal structure. The X-ray crystal structure reveals the construction of helical assemblies with opposite handedness for (+)- and (-)-chiral anion reformed gelators. The appropriate counteranion driven ion-pair-assisted hydrogen-bonding interactions are found responsible for the helical bias control in this C-3-symmetric gelator.

PVAc/PEDOT:PSS/graphene-iron oxide nanocomposite (GINC): an efficient thermoelectric material - Dey, Abhijit; Maity, Arunava; Khan, Md Abdul Shafeeuulla; Sikder, Arun Kanti; Chattopadhyay, Santanu (RSC Advances, 2016)
A green method for the synthesis of a graphene-iron oxide nanocomposite (GINC) and its PVAc based polymer nanocomposites was reported in an earlier communication. The fabricated PVAc-GINC film exhibited a conductivity of 2.18 x 104 S m(-1) with a Seebeck coefficient of 38.8 mu V K-1. Hence, the power factor (PF) reached a value of 32.90 mu W m(-1) K-2 which is 27 fold higher than a thermoelectric material based on a PVAc-graphene composite as reported in the contemporary literature. In continuation of the above mentioned study, PEDOT:PSS was used to further enhance the power factor (PT) and figure of merit (ZT) of the system. During evaluation, a PEDOT: PSS/GINC composite (5 : 95) showed a remarkable increase in various thermoelectric properties like electrical conductivity (8.0 x 10(4) S m(-1)) with a Seebeck coefficient of 25.42 mu V K-1 and thermal conductivity 0.90 m(-1) K-1. Hence PF and ZT reach up to 51.93 mW m(-1) K-2 and 0.017, respectively. To improve the mechanical strength of the polymer composite, cellulose fibre was also employed. By the addition of cellulose fibre, though the mechanical strength of the composite increases the PF reaches 5.6, which is 10 times lower than the PEDOT:PSS/GINC composite.

Tuning emission responses of a triphenylamine derivative in host-guest complexes and an unusual dynamic inclusion phenomenon - Gangopadhyay, Monalisa; Mandal, Amal K.; Maity, Arunava; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Journal of Organic Chemistry, 2016)
A newly synthesized triphenylamine derivative (1Cl(3)) shows significant differences in inclusion complex formation with two different macrocyclic hosts, cucurbit[7]uril (CB[7]) and beta-cyclodextrin (beta-CD). Detailed investigations by NMR spectroscopy reveal that CB[7] forms a 1:3 host-guest complex ([1 center dot 3{CB[7]}]Cl-3) in which three arms of 1Cl(3) are bound to three host molecules. On the other hand, beta-CD forms a dynamic 1:1 inclusion complex ([1 center dotbeta-CD]Cl-3) by binding to only one of the three arms of 1Cl(3) at a given time. The formation of a 1:1 host-guest complex with beta-CD and 1:3 host-guest complex with CB[7] was also confirmed from the results of the isothermal titration calorimetric studies. Interestingly, 1Cl(3) exhibits a rare dual emission property in solution at room temperature with the lower and higher energy bands arising from a locally excited state and an intramolecular charge-transfer transition, respectively. The difference in inclusion complex formation behavior of 1Cl(3) with the two macrocyclic hosts results in the stabilization of different emission states in the two inclusion complexes. The fundamental difference in the electrostatic surface potentials, cavity polarities, and shapes of the two macrocyclic hosts could account for the formation of the different inclusion complexes with distinct luminescence responses.

Chiral discrimination through h-1 nmr and luminescence spectroscopy: dynamic processes and solid strip for chiral recognition - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Rajamohanan, P. R.; Ravindranathan, Sapna; Das, Amitava (Chemistry-A European Journal, 2017)
The appropriate choice of the host molecules with well-defined optical activity (S-H/R-H) helps in the differentiation between two secondary ammonium ion-derivative guest molecules with different optical activities (R-G/S-G) based on the fluorescence resonance energy transfer (FRET)based luminescence responses. Crown ether-based host molecules with opposite chiral configurations (R-H, S-H) have been derived from 1,1'-bi-2-naphthol (BINOL) derivatives that have axially chiral biaryl centers. These chiral crown ethers form host-guest complexes (i.e., [2] pseudoro-taxanes) with chiral secondary ammonium ion derivatives (R-G, S-G). NMR spectroscopic studies show that the complexes are in a dynamic equilibrium in solution. Results of the H-1 NMR and fluorescence spectroscopic studies indicate a head-on orientation of the host and guest in the [2] pseudorotaxanes. The difference in the efficiency in the FRET-based responses between anthracene and the BINOL derivatives allow efficient chiral discrimination of the guests. Isothermal titration calorimetry and NMR investigations reveal that inclusion complexes between hosts and guests of the same chirality (R-H center dot R-G, S-H center dot S-G) are more stable relative to those of opposite chirality (R-H center dot S-G, S-H center dot R-G). However, FRET-based energy-transfer efficiency is higher for R-H center dot S-G and S-H center dot R-G complexes. NMR spectroscopic studies show that the relative orientation of the guest in the host cavity is significantly different when the host binds a guest of the same or opposite chirality; furthermore, the latter is more favorable for FRET, thus enabling discrimination between enantiomers. Interestingly, chiral discrimination of guest ions could also be achieved by using silica surfaces modified with chiral host molecules.

Cucurbit[7]uril induced formation of fret-enabled unilamellar lipid vesicles - Kushwaha, Shilpi; Maity, Arunava; Gangopadhyay, Monalisa; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Langmuir, 2017)
A unique fluorescence resonance energy transfer (FRET) process is found to be operational in a unilamellar lipid self-assembly in the aqueous phase. A newly synthesized naphthyl based long chain lipid derivative [N-(naphthalene-1-ylmethyl)tetradecane-1-ammonium chloride, 14NA(+)] forms various self-assembled architectures in the aqueous phase. Controlled changes in lipid concentration lead to a transition of the self-assemblies from micelles to vesicles to rods. In the presence of cucurbit[7]uril (CB7), 14NA(+) forms a host-guest [2]pseudorotaxane complex (CB7(sic)14NA(+)) and secondary interactions lead to the formation of a lipid bilayer with hydrophobic pockets situated in between the layers. The change in the structure of 14NA(+) assemblies, interaction with CB7 and formation of supramolecular assemblies of CB7(sic)14NA(+) were examined using light scattering, spectroscopic, and microscopic techniques. Entrapment of a luminescent dye, anthracene within the hydrophobic bilayer of the supramolecular assembly CB7(sic)14NA(+) favors a modified luminescent response due to an efficient FRET process. Further, the FRET process could be controlled by thermal and chemical stimuli that induce transformation of unilamellar vesicles.

Impact of half-crown/two carbonyl:-Ca2+ metal ion interactions of a low molecular weight gelator (LMWG) on its fiber to nanosphere morphology transformation with a gel-to-sol phase transition - Maity, Arunava; Dey, Ananta; Si, Mrinal Kanti; Ganguly, Bishwajit; Das, Amitava (Soft Matter, 2018)
We report here a smart functional low molecular weight gelator (LMWG) L, containing an unusual metal ion coordination site, i.e. ``half-crown/two carbonyl''. The gelator L shows excellent gelation behavior with typical fibrillar morphology in acetonitrile, methanol and ethanol media. Upon Ca2+ ion binding with its ``half-crown/two carbonyl'' coordination site, the acetonitrile gel of L exhibits a fiber to nanosphere morphology transformation along with a gel-to-sol phase transition as confirmed by microscopic investigation and by direct naked eye visualization, respectively. The mechanism involved in this morphology transformation and gel-to-sol phase transition process was studied thoroughly with the help of computational calculations and various spectroscopic experiments and discussed.

Water induced morphological transformation of a poly(aryl ether) dendron amphiphile: helical fibers to nanorods, as light-harvesting antenna systems - Maity, Arunava; Dey, Ananta; Gangopadhyay, Monalisa; Das, Amitava (Nanoscale, 2018)
Self-assembly of suitable molecular building blocks is an efficient and convenient approach to generate nanomaterials with various morphologies and functions. Moreover, understanding the nature of molecules and controlling factors of their self-assembly process is crucial in fundamental aspects of molecular self-assembly which provide insights into the design of new assemblies with functional nano-architectures. To this end, the present study reports water induced self-assembled multifaceted morphology formation and the plausible pathway of the morphology transformation of a single poly(aryl ether) dendron amphiphile 1(D). In THF, 1(D) self-assembles into helical fibers. However, with an increase in the water fraction in its THF solution, the morphology changes to nanorods through an intermediate scroll-up pathway of exfoliated fibers. The nanorod formation and transformation of 1(D) are investigated using various microscopy and spectroscopy techniques, which indicate that it has highly ordered multilayered arrays of 1(D) molecules. Finally, these multilayered arrays of 1(D) nanorods are exploited for constructing a model light-harvesting system via the incorporation of small quantities of two newly designed BODIPY based molecules as energy acceptors and 1(D) as an antenna chromophore.